Farmers’ Perceptions and Behavior which Affecting the Adoption Rate of KUB Chickens - Iif Syarifah; Sitti Nurani Sirajuddin; Syahdar Baba; Mukhamad Najib (Indonesian Center for Animal Research and Development (ICARD), 2023)
KUB chicken as a superior breed produced by Indonesian Agency for Agricultural Instrument Standardization (IAAIS) becomes one of the solutions in an effort to increase the need for animal protein. KUB chicken breeds have been successfully disseminated to all provinces in Indonesia. Thus the rate of adoption and behavior of breeders in maintaining the sustainability of KUB chicken rearing needs to be analyzed because the breeds that are disseminated may not be successfully developed in a certain area. This research will collaborate between the two theories;